Fault-Diagnosis Systems An Introduction from Fault Detection to Fault Tolerance - Isermann, Rolf. (Springer Berlin Heidelberg : Imprint: Springer, 2006)
Supervision, health-monitoring, fault detection, fault diagnosis and fault management play an increasing role for technical processes and vehicles, in order to improve reliability, availability, maintenance and life-time. For safety-related processes fault-tolerant systems with redundancy are required in order to reach comprehensive system integrity. This book gives an introduction into the field of fault detection, fault diagnosis and fault-tolerant systems with methods which have proven their performance in practical applications. It guides the reader in a structured tutorial style: supervision methods, reliability, safety, system integrity and related terminology; fault detection with signal-based methods for periodic and stochastic signals; fault detection with process model-based methods like parameter estimation, state estimation, parity equations and principal component analysis; fault diagnosis with classification and inference methods; fault-tolerant systems with hardware and analytical redundancy; many practical simulation examples and experimental results for processes like electrical motors, pumps, actuators, sensors and automotive components; end-of-chapter exercises for self testing or for practice. The book is dedicated to graduate students of electrical, mechanical, chemical engineering and computer science and for practising engineers.